A study on PID tuning for liquid flow using Ziegler-Nichols and Tyreus-Luyben techniques / Sharifah Umairah Syed Supiyan - Syed Supiyan, Sharifah Umairah (2023)
This research investigates the effectiveness of different PID tuning methods for liquid flow process control using the Liquid Flow Process Control Training System (Model SE270-1). This study focuses on comparing two established tuning methods, namely Ziegler-Nichols (Z-N) and Tyreus-Luyben (T-L). Despite the widespread use of PID controllers in industrial flow control systems, determining the optimal tuning parameters remains challenging, often resulting in unstable system responses and inefficient process control. This research systematically evaluates both tuning methods through experimental analysis and performance comparison.